Clinical impact of matrix‐assisted laser desorption ionization‐time of flight mass spectrometry combined with antimicrobial stewardship interventions in patients with bloodstream infections in a Japanese tertiary hospital. Issue 5 (21st March 2019) - Niwa, Takashi; Yonetamari, Jun; Hayama, Nozomi; Fujibayashi, Ayasa; Ito‐Takeichi, Syuri; Suzuki, Keiko; Ohta, Hirotoshi; Niwa, Ayumi; Tsuchiya, Mayumi; Yamamoto, Masayo; Hatakeyama, Daijiro; Hayashi, Hideki; et al.
Summary: Background: Matrix‐assisted laser desorption ionization‐time of flight mass spectrometry (MALDI‐TOF MS) has the potential to permit early organism identification and optimization of antibiotic therapy. However, MALDI‐TOF MS combined with antimicrobial stewardship is available at only a limited number of institutions. Here, we evaluated the clinical impact of implementing MALDI‐TOF MS combined with antimicrobial stewardship intervention in patients with bloodstream infections. Methods: We conducted a single‐centre, prospective cohort study to evaluate the clinical impact of implementing MALDI‐TOF MS combined with antimicrobial stewardship intervention in patients with bloodstream infections. Processes and clinical outcomes in patients with bloodstream infections were compared before and after implementation of MALDI‐TOF MS. Results: Compared with the conventional identification method, MALDI‐TOF MS combined with antimicrobial stewardship intervention significantly decreased the time to organism identification (48.6 ± 46.0 hours vs 78.1 ± 38.9 hours, P < 0.001), effective antimicrobial therapy (12.9 ± 19.0 hours vs 26.2 ± 44.8 hours, P < 0.001) and optimal antimicrobial therapy (53.3 ± 55.0 hours vs 91.7 ± 88.7 hours, P < 0.001. Moreover, the rate of clinical failure (14.0% vs 33.3%, P < 0.001) and incidence of adverse events (7.5% vs 23.9%, P < 0.001) was lower in the MALDI‐TOF MS group than in the conventional identification group. A multivariate Cox proportional hazard analysis indicated that implementation of MALDI‐TOF MS was a protective factor against clinical failure in patients with bloodstream infections (hazard ratio, 0.61; 95% confidence interval, 0.38‐0.99; P = 0.047). Conclusions: Implementation of the MALDI‐TOF MS combined with antimicrobial stewardship intervention facilitated early optimization of antimicrobial therapy with a remarkable concomitant reduction in clinical failure and adverse events in patients with bloodstream infections.